A educação ambiental na escola municipal Flávio Alves em Gurinhatã/MG: Percepções e ações - Silva, Marcia Maciel (2024)
This research aims to understand how Environmental Education is developed in a rural school in the municipality of Gurinhatã, Minas Gerais. The general objective involves understanding the school community's view on the importance of environmental education. Understanding how the Flávio Alves School provides means for reflection about the causes and effects of environmental degradation and how it enables them to change their behavior and, consequently, actions and attitudes that seek sustainability and conservation of the environment in which they live. In this sense, the specific objectives are: to analyze the view of the school community (students, teachers, parents, managers, and school staff) on the environmental issue and its importance; to verify the pedagogical practices related to Environmental Education in this school; describe how teachers at this school are trained about Environmental Education. The qualitative and quantitative method was used to develop the research. The methodology used to develop this research was exploratory through the application of semi-structured questionnaires with questions related to the institution's employees' view of the development of Environmental Education at the Flávio Alves school, as well as the view of teachers, students, and family members about the process training students in Environmental Education. The results achieved were that students do not understand what Environmental Education is conceptually, but carry out practical activities such as disposing of waste in the correct place. Teachers lack continued training in the area and methodological resources and infrastructure to work on the topic, but even in the face of challenges, they develop projects related to Environmental Education.